Penerapan E-Learning Menggunakan Media Edmodo dalam Pembelajaran Fisika Berbasis Nilai Karakter untuk Meningkatkan Hasil Belajar pada Konsep Usaha dan Energi - Nismawati A Haruna; Dewa Gede Eka Setiawan; Abdul Haris Odja (Physics Education Research Journal, 2021)
This study aims to test the application of e-learning using edmodo media in learning physics based on character values to improve student learning outcomes in work and energy materials. This type of research is an experiment, using the One Group Pretest-Posttest Design design. The instrument used in this study was a pretest and posttest questions consisting of 12 question numbers to test the improvement of student learning outcomes using e-learning using edmodo media. The pretest value data normality test using the Kolmogorov-Smirnov test resulted in 0.035, and for the posttest value obtained 0.457. The results showed an increase in student learning outcomes with an average gain value of 0.82 which is included in the high criteria. The results of the data hypothesis analysis were obtained from the pretest and posttest values based on the output "statistical test" known to Asymp. Sig (2-tailed) is 0.00. (0.05). Based on the results of the hypothesis test, it can be concluded that there is an increase in student learning outcomes by using e-learning using edmodo media in physics learning based on character values on business and energy materials.